Lucky breaks - Patron, Susan (Atheneum Books for Young Readers, 2009)
Having reached the mature age of eleven in the tiny California town of Hard Pan (population 43), Lucky discovers that there is still much to learn about friendship, parental trust, and the Milky Way galaxy.